The Influence Job Training and Work Discipline Regarding the Perfomance of Employees in the PT. Integra Indocabinet Sidoarjo - Ardiansyah, Dhava Candra; Adiwati, Mei Retno (PT FORMOSA CENDEKIA GLOBAL, 2023)
Human resources are crucial to a company's success in achieving its objectives. and success. One step that can be taken is to implement job training and work discipline to have high worker productivity. The purpose of this study is to ascertain how PT Integra Indocabinet Sidoarjo employees perform in relation to job training and work discipline. The approach is quantitative in nature and data collection uses a questionnaire with a Likert scale measuring instrument. This population consists of the production employees of PT Integra Indocabinet, with a total of 100 employees. The sampling techniques used are probability sampling technique and simple random sampling technique. Structural Equation Modeling (SEM) is used in data analysis with SmartPLS software. Based on the findings of the research that was done: 1. Job training makes a substantial contribution to and has the potential to improve employee performance at PT. Integra Indocabinet Sidoarjo. 2). Discipline contributes greatly to employee performance at PT Integra Indocabinet Sidoarjo and can have a positive impact on employee performance.